Rolling dopant and strain in Y-doped BiFeO3 epitaxial thin films for photoelectrochemical water splitting. Issue 1 (December 2018) - Haydous, F.; Scarisoreanu, N.; Birjega, R.; Ion, V.; Lippert, T.; Dumitrescu, N.; Moldovan, A.; Andrei, A.; Teodorescu, V.; Ghica, C.; Negrea, R.; Dinescu, M.
Abstract We report significant photoelectrochemical activity of Y-doped BiFeO3 (Y-BFO) epitaxial thin films deposited on Nb:SrTiO3 substrates. The Y-BFO photoanodes exhibit a strong dependence of the photocurrent values on the thickness of the films, and implicitly on the induced epitaxial strain. The peculiar crystalline structure of the Y-BFO thin films and the structural changes after the PEC experiments have been revealed by high resolution X-ray diffraction and transmission electron microscopy investigations. The crystalline coherence breaking due to the small ionic radius Y-addition was analyzed using Willliamson-Hall approach on the 2θ-ω scans of the symmetric (00 l ) reflections and confirmed by high resolution TEM (HR-TEM) analysis. In the thinnest sample the lateral coherence length (L∥ ) is preserved on larger nanoregions/nanodomains. For higher thickness values L∥ is decreasing while domains tilt angles (α tilt ) is increasing. The photocurrent value obtained for the thinnest sample was as high as Jph = 0.72 mA/cm2, at 1.4 V(vs. RHE). The potentiostatic scans of the Y-BFO photoanodes show the stability of photoresponse, irrespective of the film's thickness. There is no clear cathodic photocurrent observation for the Y-BFO thin films confirming the n-type semiconductor behavior of the Y-BFO photoelectrodes.